Perancangan Aplikasi Sistem PPDB InSchool dalam Mendukung Proses Digitalisasi Sekolah - Gilang Raga Yudistira; Muhammad Zaidan Azzahir; M. Rafif Akbar Zhafiri; Rizky Basatha; Nisa Dwi Septiyanti (UNIVED Press, 2026)
The development of technology in Indonesia, especially in the field of education, has now brought convenience in carrying out activities related to education, for example in the PPDB (New Student Admission) activities where many schools still carry out PPDB activities offline. This activity feels less effective and efficient in the current digital era, so a system is needed that can facilitate the PPDB process in all schools, especially in Indonesia. By using the PPDB application, it is hoped that the schools concerned can adapt to the increasingly advanced technological era and not be fixated on the old, outdated system. This research was compiled using the Research and Development (R&D) research method with a Waterfall approach that includes several stages that must be carried out, including needs analysis, system design, application implementation, system testing, and maintenance. And for the testing phase, using blackbox testing aims to measure the ability of our application to function and run well or not. This research is expected to assist in the implementation of PPDB activities. This system is designed and designed using Visual Basic, then for database processing using MySQL. We designed this application to be as simple and as simple as possible so that it is easy to use by students and schools that have access to the application. This application is expected to inspire other schools that have not yet implemented an online PPDB system.